(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
On the basis of a study of both ancient and modern toponyms from Spain, this paper focuses on some small but possibly significant aspects of the pre-Roman languages of the Iberian Peninsula.